Value of the spectrum for local mobile communication networks: Insights into awarding and pricing the 5G spectrum bands - Marja Matinmikko-Blue; Seppo Yrjölä; Petri Ahokangas; Veikko Seppänen; Heikki Hämmäinen; Risto Jurva (International Telecommunications Society (ITS), 2019)
Spectrum management decisions made by the regulators aim at maximizing the value of spectrum, its efficient utilization and benefits to the society. A major debate in spectrum management globally is currently focusing on 5G spectrum bands and their awards. In fact, several countries have recently made their first 5G spectrum awards decisions, which will have a long-term impact on the mobile communication market. This paper analyses recent 5G spectrum decisions from the spectrum valuation view point and discusses the emerging role of local 5G networks to serve the needs of different vertical sectors. Special attention is put on the awarding and pricing of 5G spectrum and recommendations are given on new pricing mechanisms that take into account the emergence of local 5G networks by different stakeholders. The results highlight the divergence in the spectrum management approaches that the regulators in different countries have taken where the first 5G spectrum decisions have continued to strengthen the mobile network operator (MNO) market dominance while the most recent planned decision aim at opening the mobile market to new local entry through local spectrum access rights.
Keywords: 330